Triphenylamine derivative and preparation method thereof, photochromic film material and preparation method and application thereof - MU YINGXIAO; JI SHAOMIN; LIAO LIYUN; HUO YANPING; LUO XUWEI (2023)
The invention discloses a triphenylamine derivative, a preparation method of the triphenylamine derivative, a photochromic thin film material, a preparation method of the photochromic thin film material and application of the photochromic thin film material. According to the invention, a triphenylamine group is used as a donor structure to connect different acceptor groups R, a guest material is synthesized through a Suzuki reaction, and a host material is polymethyl methacrylate (PMMA). The photostimulus response thin film material with a photochromic phenomenon can be obtained through a subject-object doping method, and the photostimulus response thin film material shows different luminescence colors before and after being irradiated by a 365nm ultraviolet lamp. The thin film material capable of emitting light and changing color under illumination can be applied to the aspects of display, information encryption, anti-counterfeiting and the like. The preparation method is simple and easy to operate, and a ne